Three-dimensional characteristics of nystagmus induced by low frequency in semicircular canals of healthy young people - Huang, Xiaobang; Zhang, Xueqing; Deng, Qiaomei; Li, Shanshan; Liu, Qiang; Wen, Chao; Wang, Wei; Chen, Taisheng (Frontiers in Neuroscience, 2024)
Objective The study aimed to analyze the three-dimensional characteristics of nystagmus induced by different semicircular canal combinations in healthy young people, and to determine the reference range of nystagmus slow phase velocity (SPV) and its asymmetry. Materials and methods Fifty-two healthy volunteers (26 males and 26 females, aged 17–42 years, average 23.52 ± 6.59), were recruited to perform the manual triaxial rotation testing with a 3D-Videonystagmography (3D-VNG) device (VertiGoggles (ZT-VNG-II), Shanghai ZEHNIT Medical Technology Co., Ltd., Shanghai, China) using a 0.3 Hz prompt beat and a 90° amplitude, respectively. The induced nystagmus around the Z-, X-, and Y-axes were recorded in the yaw, pitch, and roll planes. The directions and slow phase velocities of the horizontal, vertical, and torsional components of the induced nystagmus under different semicircular canal combinations (the left lateral and right lateral semicircular canal combination, bilateral anterior semicircular canals, bilateral posterior semicircular canals combination, and the anterior and posterior semicircular canals combination of each ear), as well as their asymmetry, were taken as the observation indexes to analyze the characteristics of the nystagmus vectors of different combinations. Results Fifty-two healthy volunteers had no spontaneous nystagmus. The characteristic nystagmus was induced by the same head movement direction in all three axial rotation tests. The SPVs of the left and right nystagmus were 44.45 ± 15.75°/s and 43.79 ± 5.42°/s, respectively, when the subjects’ heads were turned left or right around the Z-axis (yaw). The SPVs of vertically upward and downward nystagmus were 31.67 ± 9.46°/s and 30.01 ± 9.20°/s, respectively, when the subjects’ heads were pitched around the X-axis (pitch). The SPVs of torsional nystagmus, with the upper poles of the eyes twisting slowly to the right and left ears (from the participant’s perspective), were 28.99 ± 9.20°/s and 28.35 ± 8.17°/s, respectively, when the subjects’ heads were turned left or right around the Y-axis (roll). There was no significant difference in the SPVs of nystagmus induced by the same rotation axis in two opposite directions (p > 0.05). The reference ranges for the slow phase velocities (SPVs) of nystagmus induced by the triaxial rotation testing were as follows: For the Z-axis (yaw), the SPVs were 13.58–75.32°/s for leftward head rotation and 13.56–74.02°/s for rightward head rotation. For the X-axis (pitch), the SPVs were 13.13–50.21°/s for upward head nystagmus and 11.98–48.04°/s for downward head nystagmus. For the Y-axis (roll), the SPVs were 10.97–47.02°/s for the left-sided head rotation and 12.34–44.35°/s for the right-sided head rotation. Conclusion This study clarified the three-dimensional characteristics of nystagmus induced by different semicircular canal combinations in healthy young people. It also established a preliminary reference range of SPVs and SPV asymmetry of nystagmus induced by the vertical semicircular canal. It can further provide a basis for the mechanism of semicircular canal-induced nystagmus and the traceability of nystagmus in patients with otogenic vertigo. It is shown that the portable 3D-VNG eye mask can be used for the manual triaxial rotation testing to achieve the evaluation of the low-frequency angular vestibulo-ocular reflex (aVOR) function of the vertical semicircular canal, which is convenient, efficient, and practical.